Janus Microgels with Tunable Functionality, Polarity, and Optical Properties. Issue 2 (15th November 2016) - Xu, Wenwen; Wei, Menglian; Serpe, Michael J.
Abstract : A facile self‐assembly method is presented to prepare poly( N ‐isopropylacrylamide)‐based microgels modified anisotropically with gold nanoparticles (Au NPs) to yield Janus microgels. Transmission electron microscopy is used to confirm that microgels are selectively coated on one or both sides with Au NPs. This approach is able to generate microgels with the same (monopolar) or different (bipolar) charge on either side of the microgel surface. The optical properties of the Au NPs adsorbed to the microgel surface are also characterized as a function of temperature and pH. It is found that the plasmon absorption of the Au NPs depends on each, which can be explained by the microgel's solvation state dictating the distance between the Au NPs. The surface adsorption behavior of the monopolar and bipolar microgels is also investigated, and it is demonstrated that the bipolar microgels exhibit enhanced surface adsorption compared to the monopolar microgels. Finally, it is shown that the Janus microgel assembly can be controlled by modifying the Au NPs of at least two different sets of Janus microgels with complementary DNA sequences. The work here can find utility for generating surface adsorbed materials with controllable optical properties, sensors, and for studying fundamental behavior of self‐assembling materials. Abstract : A facile self‐assembly method is presented to prepare poly( N ‐isopropylacrylamide)‐based Janus microgels with different polarities that exhibit unique surface adsorption behavior and optical properties. It is also shown that the Janus microgels can be utilized as building blocks for DNA guided self‐assembly.